Initial Findings Into The Financial Impact Of Corporate Governance: Evidence From PalestinianListed Companies - Abdulsamad M. A. Abusonaina; Mohd Shukor Harun; Adel Abusharar (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA